Green Energy in Ukraine: State, Public Demands, and Trends - Aleksandra Kuzior (MDPI AG, 2021)
The main purpose of this paper is to analyze and address the challenges of implementing green energy in Ukraine, in particular, to identify its advantages and disadvantages. The implementation of solar renewable sources—stations, panels, and batteries—is emphasized. The results of sociological surveys of Ukrainian public opinion on environmental issues, in particular, energy issues, are presented. The existence of public demand for renewable energy and the readiness of the population to use renewable energy sources are identified. A strategy for strengthening the country’s energy independence in the face of new globalization challenges is defined. General scientific methods as well as special methods were used in this paper: statistical analysis, secondary analysis of data from sociological studies of public institutions, and desk analysis of documents and reports from public services. In this paper, it is concluded that Ukraine is geographically and territorially attractive for green energy development and investment. It is important that there is a public and state demand in the country to strengthen the country’s energy security, in particular, through the introduction of renewable energy sources. Therefore, despite drawbacks and obstacles, green energy in Ukraine has great prospects.